Defining a core data set for the economic evaluation of precision oncology - Pollard, S; Weymann, D; Chan, B; Ehman, M; Wordsworth, S; Buchanan, J; Hanna, TP; Ho, C; Lim, HJ; Lorgelly, PK; Raymakers, AJN; McCabe, C; et al. (Elsevier, 2022)
Objectives: Precision oncology is generating vast amounts of multiomic data to improve human health and accelerate research. Existing clinical study designs and attendant data are unable to provide comparative evidence for economic evaluations. This lack of evidence can cause inconsistent and inappropriate reimbursement. Our study defines a core data set to facilitate economic evaluations of precision oncology.